2016
DOI: 10.1039/c5cc09930g
|View full text |Cite
|
Sign up to set email alerts
|

Cyclization and unsaturation rather than isomerisation of side chains govern the selective antibacterial activity of cationic-amphiphilic polymers

Abstract: Membrane-active agents represent a promising alternative to overcome antibiotic resistance. Here, we report cationic-amphiphilic polymers with variations in the side chain architecture such as cyclization, isomerization and unsaturation that resulted in potent antibacterial activity and low mammalian cell toxicity with a membrane-active mode of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 18 publications
2
46
0
Order By: Relevance
“…We have reported the synthesis and characterization of cationic-amphiphilic macromolecules based on poly(isobutylene- alt - N -alkyl maleimide) backbone previously [ 30 32 ]. The detailed synthetic protocols and complete characterization have been reported previously [ 30 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have reported the synthesis and characterization of cationic-amphiphilic macromolecules based on poly(isobutylene- alt - N -alkyl maleimide) backbone previously [ 30 32 ]. The detailed synthetic protocols and complete characterization have been reported previously [ 30 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…We have reported the synthesis and characterization of cationic-amphiphilic macromolecules based on poly(isobutylene- alt - N -alkyl maleimide) backbone previously [ 30 32 ]. The detailed synthetic protocols and complete characterization have been reported previously [ 30 32 ]. These macromolecules selectively displayed potent antibacterial efficacy against actively growing planktonic bacteria with minimal toxicity to mammalian cells with membrane-active mode of action as described earlier [ 30 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Related advances have been made by the Haldar group using alternating copolymers of maleimide and isobutylene. 128 These findings suggest that alternating sequence is a prudent and perhaps under-appreciated design strategy. Very recently, Perrier and co-workers undertook a detailed study of sequence control in antimicrobial poly(acrylamide)s bearing hydrophobic isopropyl and cationic aminoethyl side chains.…”
Section: Remaining Questionsmentioning
confidence: 99%
“…[6] Haldar similarly showed that cyclization and unsaturation of the hydrophobic groups in amphiphilic polymers are important determinants of bioactivity. [7] Removing pendant hydrophobic groups altogether,L ienkamp and co-workers recently reported polyoxanorbornenes with pendant zwitterionic groups where the backbone imparted hydrophobicity in- stead. [8] Similarly,P alermo and co-workers reported selfimmolative poly(benzyl ether)s with pendant oligo(ethylene glycol) and thioether-linked primary amines,w hich are both nominally hydrophilic, whereas the backbone is intensely hydrophobic.…”
mentioning
confidence: 99%